2017
DOI: 10.1002/pros.23325
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells as a Marker for Progression‐free Survival in Metastatic Castration‐naïve Prostate Cancer

Abstract: In this explorative study, CTCs were detected in 98% of M1 patients and detection of EGFR in CTCs was strongly associated with poor outcome, which indicated that phenotypical analysis of CTC could be a promising prognostic marker of ADT-response in castration-naïve metastatic PC patients. Prostate 77:849-858, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…We have previously reported the prognostic value of detection of EGFR and ARV7 in hormone-sensitive metastatic prostate cancer, in a patient cohort partly overlapping the present study [40,41]. Our previous data could not be confirmed in this study where the multiplex gene expression analysis enables more careful normalization and accurate exclusion of samples with low CTC content.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We have previously reported the prognostic value of detection of EGFR and ARV7 in hormone-sensitive metastatic prostate cancer, in a patient cohort partly overlapping the present study [40,41]. Our previous data could not be confirmed in this study where the multiplex gene expression analysis enables more careful normalization and accurate exclusion of samples with low CTC content.…”
Section: Discussioncontrasting
confidence: 75%
“…CTCs were isolated from blood and detected using the AdnaTest ProstateCancerSelect/Detect (Qiagen Hannover GmbH, Langenhagen, Germany) as previously described [41]. Briefly, patient blood samples were collected immediately prior to surgery in AdnaCollect tubes and kept refrigerated (4 • C) for no more than 24 h until CTC isolation.…”
Section: Ctc Isolation and Cdna Synthesismentioning
confidence: 99%
“…We also add 1 point in cases of visceral metastasis. M1 stage showed a strong association with early progression, and circulating tumor cells were detected more frequently in M1 patients . In localized prostate cancer, circulating tumor cells did not show a significant correlation with pathological T stage, and no studies have proven that circulating tumor cells predict unfavorable prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…These two integrin markers were increased with tumor progression from localized T1-T2 tumors (44 patients) to hormone-refractory metastatic tumors (28 patients) and were associated with decreased metastasis progression free survival [63]. In a study of 53 patients, CTC enumeration using both the CellSearch method and the AdnaTest kit isolating EpCAM + and HER2 + cells demonstrated that EpCAM + cell numbers in the circulation correlated with the presence of metastases [64]. Interestingly, E-cadherin expression was associated with bone metastasis in 109 patients, but not soft tissue metastasis in 56 patients [65], suggesting that mesenchymal-epithelial transition (a reversion from EMT) may be occurring, which is required for escape from the dormancy normally associated with bone metastatic growth.…”
Section: Cancer Stem Cells Control Colonization and Metastatic Growthmentioning
confidence: 99%
“…CD117 + CTC numbers, in particular, remained high 3 months after radical prostatectomy in the circulation of 12 patients who experienced biochemical recurrence 6–18 months later [37], indicating that CSCs in the circulation may be used to predict therapeutic failure earlier. In another study of 50 patients with CTCs measured before and after androgen deprivation therapy by the CellSearch apparatus, it was shown that CTC levels were associated with rising PSA and decreased progression free survival [64]. In addition, staining of potential CTCs from 27 patients with metastatic castration-resistant prostate cancer demonstrated that patients with neuroendocrine prostate cancer have significantly different CTCs with lower AR and cytokeratin expression and smaller size [67].…”
Section: Cancer Stems Cells In Recurrence and Resistance To Treatmentmentioning
confidence: 99%